Ampicillin administration and the incidence of severe acute kidney injury in patients with sepsis - Xinyao Luo; Peiyan Sun; Dingyuan Wan; Tinghang Yang; Yupei Li; Baihai Su (Renal Failure)
Background Acute kidney injury (AKI) affects 40–50% of septic patients, with limited prevention options. This study investigates the relationship between early ampicillin administration and severe AKI in septic patients.Methods A retrospective cohort study using the MIMIC-IV database (2008–2019) was conducted. The primary outcome was severe AKI, and secondary outcomes included continuous renal replacement therapy, in-hospital death, and any-stage AKI. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were used to adjust for confounders. Multivariate regression explored the association between ampicillin and severe AKI incidence, and subgroup analyses were performed.Results A total of 17,676 septic patients were included, with 915 matched pairs after PSM. Ampicillin administration was associated with a reduced risk of severe AKI (OR = 0.78; 95% CI 0.68–0.90) in multivariable logistic regression, PSM (OR = 0.74; 95% CI 0.61–0.92), and IPTW (OR = 0.77; 95% CI 0.74–0.81). Incidence of acute kidney disease was lower in the ampicillin group (OR = 0.77; 95% CI 0.61–0.97). Mortality rates at 30 and 90 days were also lower (HR = 0.69; 95% CI 0.55–0.86 and OR = 0.67; 95% CI 0.55–0.82). The protective effect was more pronounced in female and older patients.Conclusions Early ampicillin administration within 48 h of ICU admission is associated with reduced severe AKI and improved short-term renal outcomes in septic patients. Further studies are needed to confirm these findings.